PENGARUH EKSTRAK ETANOLIK BUAH PARIJOTO (Medinilla speciosa Blume) TERHADAP KADAR GULA DARAH DAN FUNGSI SEKSUAL TIKUS JANTAN GALUR WISTAR MODEL DIABETES MELLITUS KRONIK - Rina Wijayanti; Asih Puji Lestari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTChronic diabetes mellitus is a disease of increased blood glucose levels in a long time so that it can affect sexual function such as damage spermatogenesis and aphrodisiac function. Parijoto has flavonoid content. This study aimed to determine the effect of ethanolic extract of parijoto (Medinilla speciosa Blume) fruit in blood glucose level and the sexual function in alloxan-induced diabetic male rats. The design of the study was post test only control group design, 25 male wistar rats aged 2 months with BB 100-200 gram divided into 5 groups. Group 1 (normal control), group 2 (negative control) induced alloxan 100mg / kgBB, groups 3, 4, and 5 were alloxan induced and administered EEBP at doses of 100 mg / kgBW, 250 mg / kgBW, and 500 mg / kgBW. Alloxan-induced rats were left for 4 weeks to achieve chronic DM. Data analysis of blood glucose level and spermatozoa quality using one way anova followed by LSD post hoc. While aphrodisiac of introducing and climbing using one way anova continued by LSD and coitus using kruskal wallis. The results showed that there were significant differences between negative control with normal group, III, IV, and V. The effect of ethanolic extract of parijoto fruit on blood glucose level and sexual function in alloxan-induced diabetic male rats showed no difference between treatment group of 100 mg / kgBW with negative group, and there were significant differences between treatment group of 250 mg / kgBW and 500 mg / kgBW with negative group. Ethanolic extract of parijoto fruit at dose 250 mg / kgBB and 500 mg / kgBB decrease blood glucose level, improve and increase sexual function in alloxan-induced diabetic male rats.